2021
DOI: 10.1017/jfm.2021.547
|View full text |Cite
|
Sign up to set email alerts
|

Drop impact on solids: contact-angle hysteresis filters impact energy into modal vibrations

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 91 publications
(168 reference statements)
1
12
0
Order By: Relevance
“…We treat the impacting event as an inverse problem, reconstructing the impact conditions from the post-impact liquid/gas vibration frequency spectrum and modal energy partitioning. Kern, Bostwick & Steen (2021) have shown recently that for normal drop impact, the drop's liquid/gas interface vibrates in mode shapes predicted for sessile drops (Bostwick & Steen 2014;Chang et al 2015;Steen, Chang & Bostwick 2019). In this paper, we show that the same is true for oblique drop impact.…”
Section: Introductionsupporting
confidence: 69%
See 4 more Smart Citations
“…We treat the impacting event as an inverse problem, reconstructing the impact conditions from the post-impact liquid/gas vibration frequency spectrum and modal energy partitioning. Kern, Bostwick & Steen (2021) have shown recently that for normal drop impact, the drop's liquid/gas interface vibrates in mode shapes predicted for sessile drops (Bostwick & Steen 2014;Chang et al 2015;Steen, Chang & Bostwick 2019). In this paper, we show that the same is true for oblique drop impact.…”
Section: Introductionsupporting
confidence: 69%
“…During normal drop impact, , we have shown that during pinning, the drop vibrates in a linear combination of axisymmetric modes with corresponding frequencies (Kern et al. 2021). Figure 3( a ) shows that for oblique impact, the frequency spectrum consists of both the and modes.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations